1986
DOI: 10.1118/1.595822
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetry of asymmetric x‐ray collimators

Abstract: We have studied the dosimetry of an independent jaw system (provided with the Varian Clinac 2,500) using ionometric measurements performed both in air and in a water phantom. Our study shows that the effect of the independent jaw on the dose distribution is similar to that of secondary blocking except for changes produced in the collimator scatter. A system of dose calculation was developed which takes into account the changes in the collimator scatter as well as in the isodose distribution. A method is descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
7

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 0 publications
4
31
0
7
Order By: Relevance
“…Khan et al [4] have suggested that the asymmetric collimators can be considered as diverging blocks in computerized treatment planning systems for dose calculations. However, the above assumption might lead to some error in dose delivery due to the presence of backscatter radiation into the beam monitor chambers.…”
Section: Discussionmentioning
confidence: 99%
“…Khan et al [4] have suggested that the asymmetric collimators can be considered as diverging blocks in computerized treatment planning systems for dose calculations. However, the above assumption might lead to some error in dose delivery due to the presence of backscatter radiation into the beam monitor chambers.…”
Section: Discussionmentioning
confidence: 99%
“…67,68 However, measured profile data inherently contain changes in the relative scatter contribution within the phantom which are not accounted for in the current formalism. 69 Although good agreement is obtained for points close to the central axis, 67,70 errors greater than 5% can be obtained using profile data close to the edge of the field (e.g., x > 10 cm). Although calculations to points this far off-axis are unlikely to be seen in the clinic with any frequency, caution should be used when using these data for OAR.…”
Section: B1f Off-axis Ratiosmentioning
confidence: 99%
“…This effect is largest for a short SSD (1 1). Since central-axis depth doses can be measured in conventional geometry at the TBI distance and collimator scatter is almost independent of the position of the jaws for fields of the same dimensions (15), off axis depth doses were measured in a large water phantom in fields defined by the asymmetric jaws (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%